Physicochemical analysis of wastewater discharge and impact on Ganges River of major cities of North India. Issue 6 (26th April 2022) - Soni, Ramendra; Pal, Arun Kumar; Tripathi, Pooja; Jha, Pawan Kumar; Tripathi, Vijay
Abstract: The inadequate practice of discharge of wastewater into receiving water bodies alters physicochemical parameters, which ultimately disturbs the livelihood of aquatic flora and fauna. The present study was focussed on the evaluation of the efficiencies of wastewater treatment plants based on different technologies through analysing the physicochemical parameters of wastewater collected from each treatment step including inlet, outlet and downstream Ganges River in Prayagraj, Varanasi and Kanpur (India) during winter and summer seasons. The removal efficiency of the MBBR technology of Prayagraj WWTP was observed to be better than that of the ASP and UASB technologies of Varanasi and Kanpur respectively for both seasons. Correlation analysis explained the strong negative correlation of pH and DO with nearly all the parameters of the study; whereas TDS, hardness, ammonia and BOD were highly correlated with each other in each city. The factor analysis suggested the best fit amongst the physicochemical parameters, with four factors elucidating 78.00% of the total variance, which further explained that DO, TDS, total alkalinity, nitrate, COD, and temperature were the major components for pollution. The results indicated that most of the samples were not appropriate for direct discharge into water bodies and irrigation purposes and thus needed further implementation of advanced technologies in their treatment procedure. HIGHLIGHTS: Efficiencies of wastewater treatment plants based on different technologies were evaluated. Maximum COD removal was achieved by MBBR technology. MBBR technology was found to be more efficient over ASP and UASB. Conventional technologies need advancement in their treatment procedure. Graphical Abstract